Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan pada Apotek Kimia Farma 273 Samarinda - Harti Afnie; Suharno Suharno; J. Kuleh (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this research is to know the influence of service quality consisting of Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5), to Customer Loyalty at Farma Pharmacy 273 Samarinda. Analyzer used in this research is statistical test with Multiple Linear Regression method and hypothesis test using Correlation Coefficient (R), Coefficient of Determination (R2) also use F test and T test. The result of research is Y = 179,466 + 0,081 X1 + 0,690 X2 + (-0.132) X3 + (-0.075) X4 + 0.010 X5. From multiple linear regression equation it can be seen that the variable of reliability (X2) which influences positively and significantly. And the tangible (X1) and emphaty (X4) variables together do not positively and significantly affect customer loyalty. While responsiveness (X3) and assurance (X5) together have a positive effect and no significant effect on customer loyalty. There is only one variable that is most dominant positively and significantly affect customer loyalty that is reliability (reliability).Keywords: Customer Loyalty, Physical Behavior, Reliability, Responsiveness, Warranty, and Empathy.